2012
DOI: 10.1007/s00213-012-2635-y
|View full text |Cite
|
Sign up to set email alerts
|

α2- and β-adrenoceptors involvement in nortriptyline modulation of auditory sustained attention and impulsivity

Abstract: We conclude that sustained attention displays an inverse U-shaped dependence on NT, mediated-at least in part-by α(2)- and β-adrenoceptors. We speculate that low doses of NT improve performance by maximizing the phasic release of NE, while higher doses of NT would elevate tonic levels of NE, thus producing suboptimal levels of phasically released NE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Consistent with our findings, previous studies suggest that prazosin has little effect on motor impulsivity (Koskinen et al 2003; Liu et al 2009; Milstein et al 2010; Roychowdhury et al 2012). While guanfacine has been reported to decrease impulsive choice in primates (Kim et al 2012), our results are consistent with those from a recent study showing that guanfacine had no effect on decision making in rats (Pardey et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, previous studies suggest that prazosin has little effect on motor impulsivity (Koskinen et al 2003; Liu et al 2009; Milstein et al 2010; Roychowdhury et al 2012). While guanfacine has been reported to decrease impulsive choice in primates (Kim et al 2012), our results are consistent with those from a recent study showing that guanfacine had no effect on decision making in rats (Pardey et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…An oft found bell-shaped dependence of specific PFC-dependent performance on adrenergic activation (Roychowdhury et al, 2012; Sapolsky, 2015) could be interpreted as a transition from a low-energy state (state 2: quiet wake ), to state 3 ( active wake ), associated with a larger energy mobilization, stronger engagement, and improved cognitive performance (left part of the bell shape curve). At the right end of the curve would lay the transition between state 3 ( stress ) and state 4 ( FoF , right part of the bell shape), with a massive engagement of βRs in the cortex as well as in subcortical nuclei—particularly the amygdala—and consequent dysfunctional working memory, in favor of an optimal impulsive, automatic, motor response and full-fledged autonomic sympathetic response (Bouret and Sara, 2005; Hains and Arnsten, 2008; Gamo and Arnsten, 2011).…”
Section: Lc-cns Interactionsmentioning
confidence: 99%
“…It is known that NE brain levels are important for maintaining sustained attention in time, and it has been shown that low dose of nortryptiline (NE reuptake blocker) can improve the performance of rats in an auditory sustained attention tasks (Roychowdhury et al, 2012). In this line, the additional effect of repeated restraint stress could be unmasked by reboxetine (Figure 3), which might diminish the impairment in performance produced by sustained attention.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is possible that chronic stress influences attention via an additional mechanism to the NE system. The auditory pathway and mPFC are strongly regulated by cholinergic system to support sustained attention (Young et al, 2004; Schofield et al, 2011; Roychowdhury et al, 2012; Poorthuis and Mansvelder, 2013; Bloem et al, 2014). It has been reported that A1, MGN, and mPFC receive cholinergic innervation from the basal forebrain and acetylcholine modulates the neuronal activity of these brain areas during attention (Passetti et al, 2000; Kamke et al, 2005; Schofield et al, 2011; Bloem et al, 2014).…”
Section: Discussionmentioning
confidence: 99%